Sliding window neural network based sensing of bacteria in wastewater treatment plants. (February 2022) - Alharbi, Mohammed; Hong, Pei-Ying; Laleg-Kirati, Taous-Meriem
Abstract: Ensuring the performance of wastewater treatment processes is important to guarantee that the final treated wastewater quality is safe for reuse. However, bacterial concentration present along the different stages of treatment process is not easily measured routinely for the plant operators. In this paper, a moving horizon sensing approach based on neural networks is proposed to estimate the bacterial concentration in wastewater sampled along different stages of the plant. Due to the difficulties to measure the bacteria and the lack of a sufficiently large dataset, a Wasserstein generative adversarial network (WGAN) is designed to generate synthetic data. The Wasserstein critic loss is computed on a held-out validation set to evaluate the WGAN. Then, the generated data is used to train a long short term memory (LSTM) neural network that is developed to predict the biomass concentration and update the LSTM weights by a sliding window learning approach. Two datasets for WWTP are used to test the proposed method: first, effluent concentrations simulated using a benchmark simulation model no.1 (BSM) based on membrane bioreactor (MBR), where three different weather profiles of influent data were considered then, sampled data from MBR plant at King Abdullah University of Science and Technology (KAUST). Finally, the prediction results indicate that WGAN successfully generates realistic samples that are used to train the LSTM neural network. In addition, estimation performance of the proposed method is compared with a multilayer perceptron neural network (MLP-NN). Results showed that the proposed method improves the bacteria estimation performance compared to MLP-NN. Highlights: A sliding window approach for smart sensing of bacteria in WWTP is proposed. The method is based on LSTM neural network combined with WGAN for data generation. The LSTM is trained on synthetic data and tested on real WWTP data. The testing is done online while the LSTM retrain on new data. The method is evaluated on KAUST WWTP and BSM-MBR data.